PERLINDUNGAN HUKUM TERHADAP ISTRI ATAS KEKERASAN DALAM RUMAH TANGGA (Studi Kasus Putusan Pengadilan Negeri Sidoarjo Nomor 920/Pid.Sus/2021/PN.Sda) - Sucianto, Haris; Bangsu, Mohammad; Qudussalam, Abdul (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
The PKDRT Law is to provide punishment for perpetrators of domestic violence and provide a deterrent and remorseful effect so that it is hoped that it will reduce and prevent cases of domestic violence. The purpose of this research is to look at criminal protection efforts against other parties for domestic violence and to investigate criminal obligations of husbands who commit domestic violence against their wives and to study cases at the Sidoarjo District Court No.920/Pid.Sus/2021/ PN. Sda. This study uses a normative review approach and empirical methods. the prison's primary basis for these comments is the election of court No. 920/Pid.Sus/2021/PN.Sda, the statistical analysis strategy in this assessment is carried out normatively, especially contrary to court decisions or the jurisprudence. . Based on the effects of this research, it can be concluded that crime protection against various parties who oppose domestic violence consists of making recommendations to eliminate domestic violence, organizing oral exchanges, statistics and faculty on domestic violence, maintaining outreach or outreach and advocacy for domestic violence. Then the criminal charge against the husband of the perpetrator of domestic violence against his wife saw the case in the Sidoarjo District Court No. 920/Pid.Sus/2021/PN.Sda, the Panel of Judges of the Sadoarjo District Court considers that shortcut Retno Rudi Santoso was found guilty legally and convincingly of committing a crime of violence within the family sphere so that the person concerned was sentenced to imprisonment for 10 (ten) years. The judge's decision is considered less than optimal because it only gives 10 years in prison, even though the persecution committed by the suspect led to the death of the victim, it can be concluded that the judge in deciding the case is not optimal because if it refers to Article 44 of the PKDRT Law paragraph (3) the perpetrator can be charged with a maximum criminal sentence of 15 years and a fine of Rp. 45,000,000 so that the perpetrator feels deterrent and can be a lesson for husbands not to commit acts of PKDRT.